Test-retest reliability of an upper-extremity discomfort questionnaire in an industrial population - Franzblau, Alfred; Salerno, DF; Armstrong, Tom J; Werner, Robert A (Scandinavian Journal of Work, Environment & Health, 1997)
' ' OBJECTIVES ': 'Efforts to understand or to monitor upper-extremity musculoskeletal disorders among workers have usually involved the use of questionnaires. The goal of this study was to assess the test-retest reliability of an upper-extremity discomfort questionnaire among industrial workers.' ' METHODS ': 'Test-retest agreement among 148 workers was analyzed using the kappa coefficient for categorical outcomes. Values of kappa greater than 0.75 are considered excellent, values between 0.40 and 0.75 are fair to good, and values of less than 0.40 represent poor agreement beyond chance alone. Test-retest results of continuous measures (eg, visual analogue scale responses) were compared with paired t-tests.' ' RESULTS ': 'The test-retest reliability of the questionnaire used to elicit demographic information, medical history, exercise participation, and information on musculoskeletal symptoms among industrial workers appears to be good to excellent in most instances.
Keywords: ergonomics; kappa coefficient; MSD; musculoskeletal disorder; reliability; surveillance